Improved thermoelectric and mechanical performance of Sb2Te3-based materials toward the segmented operation. (July 2022) - Wu, Hao; Sun, Yuxin; Wang, Yuxuan; Qin, Haixu; Zhu, Jianbo; Zhu, Yuke; Hu, Jinsuo; Guo, Muchun; Liu, Jing; Liu, Ming; Guo, Fengkai; Zhang, Qian; et al.
Abstract: Sb2 Te3 -based material is a promising mid-temperature thermoelectric material. However, the high carrier concentration and lattice thermal conductivity of Sb2 Te3 lead to a low zT value. In this work, we choose Sb1.85 In0.15 Te2.98 and utilize Mn doping to enhance the thermoelectric performance. Mn substitution on the Sb site as the acceptor doping modulates the carrier concentration, leading to the increased power factor and the suppressed bipolar effect simultaneously. Meanwhile, the lattice thermal conductivity is also reduced. As a result, the maximum zT at 673 K reaches 1.1, compared to other advanced Sb2 Te3 -based materials. Furthermore, solid solution strengthening resulting from Mn substitution improves mechanical properties. Combined with Bi0.5 Sb1.4925 Mn0.0075 Te3 to form a segmented device, the theoretical conversion efficiency reaches 13.4% with a temperature difference of 370 K from 303 K to 673 K, highlighting the potential for mid-temperature power generation. Graphical abstract: Image 1 Highlights: Mn doping increased the power factor and suppressed the bipolar effect simultaneously. Mn doping reduced the thermal conductivity and improved mechanical properties. Theoretical efficiency for the segmented leg reached 13.4% between 303K and 673K.